Strategy for innovation in the commercialization process of clay handicrafts in the municipality of Ráquira (Revista cientifica In Vestigium Ire, 2021)
Arts and crafts are the cultural expresión of a region or a town which embodies creativitywithin a product. One of the primary economic activities of the town of Ráquira, Boyacá, Colombia is the production of clay handicrafts and heir commercialization. Since the sale of these products are done through traditional channels, the market for these products is unable to be strengthened. An analysis of the current situation of the artisanal sector and the participation of government entities that support the commercialization of these products was performed. A review of emerging trends such as E-commerce, social media, and other technological advances in developing successful businesses are part of the aspects discussed in this study.A descriptive methodology with a qualitative approach was utilized in order to analyze thecurrent situation. Dialogues with a sample population of artisans, merchants, and other actors who support the business sector of the town were recorded.Based on the results, some recommendations are provided to implement digital strategies as an innovative way of marketing and recognition. This was especially the case of businesses whose products were not accredited, providing direct contact with the target audience and therefore generating more sales at the local and regional level.
Keywords: clay handicrafts; production process; innovation; E-commerce; social media